Ångest hos hundar vid veterinärbesök: en överblick över problemet - Hjelm, Jonna (SLU/Dept. of Animal Environment and Health (until 231231), 2018)
Most dogs will at some point in their lives visit a veterinary clinic. Unfortunately, many dogs experience severe anxiety in the clinic, which not only compromises the dog’s welfare – it also poses a potential risk for the personnel at the veterinary clinic, seeing as they need to handle a frightened animal. Although ample research on the topic of fear in dogs exists, a majority of studies have a different focus, such as noise sensitivities or separation anxiety. Even if an owner has a good understanding of learning theory they might struggle to understand how to apply that knowledge to the situation at hand. This literary review aims to serve as an overview on the topic by detailing how to determine if a dog is stressed and what could cause fear of the veterinary clinic. This paper also reviews methods of training a dog, both to prevent fear and to process an already established problem. The results conclude that progress is being made both in improving as well as inventing brand new ways to measure physiological signs of anxiety, but also highlight the need to use physiological tests in combination with behavioural observations in order to achieve a reliable result. It seems like no single behaviour signifies anxiety in all dogs, which is why studies use a variety of different behaviours to reliably measure anxiety. As for fear of the veterinary clinic, it appears that many different factors such as genetics, previous experience and training can influence whether a dog develops a fear or not. However, the reason cited most commonly in studies appears to be a previous negative experience. Studies point out that even though a dog that has been handled and socialised properly from a young age is less likely to become frightened, even a perfect upbringing may not matter if a dog during its adolescence has a negative experience at the veterinary clinic. Lastly, the results show that the most common method used to train a dog with veterinary-related anxiety is to use counter-conditioning.